A Model for Primary Cilium Biogenesis by Polarized Epithelial Cells: Role of the Midbody Remnant and Associated Specialized Membranes - Labat-de-Hoz, Leticia; Rubio-Ramos, Armando; Casares-Arias, Javier; Bernabé-Rubio, Miguel; Correas, Isabel; Alonso, Miguel A. (Frontiers in Cell and Developmental Biology, 2021)
Primary cilia are solitary, microtubule-based protrusions surrounded by a ciliary membrane equipped with selected receptors that orchestrate important signaling pathways that control cell growth, differentiation, development and homeostasis. Depending on the cell type, primary cilium assembly takes place intracellularly or at the cell surface. The intracellular route has been the focus of research on primary cilium biogenesis, whereas the route that occurs at the cell surface, which we call the ‘alternative’ route, has been much less thoroughly characterized. In this review, based on recent experimental evidence, we present a model of primary ciliogenesis by the alternative route in which the remnant of the midbody generated upon cytokinesis acquires compact membranes, that are involved in compartmentalization of biological membranes. The midbody remnant delivers part of those membranes to the centrosome in order to assemble the ciliary membrane, thereby licensing primary cilium formation. The midbody remnant’s involvement in primary cilium formation, the regulation of its inheritance by the ESCRT machinery, and the assembly of the ciliary membrane from the membranes originally associated with the remnant are discussed in the context of the literature concerning the ciliary membrane, the emerging roles of the midbody remnant, the regulation of cytokinesis, and the role of membrane compartmentalization. We also present a model of cilium emergence during evolution, and summarize the directions for future research.